Semantic Analysis of Chairil Anwar's “Sendiri” Poem - Mikael Pardomuan Hutabarat; Rosmawaty Harahap (Journal of Aceh Studies, 2025)
Poetry is an important record and translation of human experience, transformed into an important and interesting structure. One type of writing that is important to a wide range of people and ages in the public eye is poetry. There are certain people who are fond of composing poetry, not just understanding it. The language of poetry is usually free and not represented by rules. Sometimes it is difficult to understand the significance of a beautiful poem because of the many metaphorical dialects used. The focal point of this study is the poem “Sendiri” by Chairil Anwar. The problem centered by the author is limited to the importance of the words in the poem. By utilizing semantic studies that highlight grammatical meaning, lexical meaning, non-literal or figurative meaning and referential meaning, this exploration is expected to be able to understand the important meaning contained in the poem “Sendiri”. The method used in this research is descriptive qualitative method. From the analysis conducted, the poem “Alone” can be examined using semantic examination. This poem talks about the feeling of isolation and silence.